MODEL LAYANAN PENDIDIKAN AGAMA HINDU UNTUK ANAK BERKEBUTUHAN KHUSUS PASCA ERUPSI GUNUNG AGUNG DI SLBN KARANGASEM - Ni Wayan Yuniastuti; Ida Bagus Putu Eka Suadnyana (UNHI PRESS, 2019)
Karangasem Extraordinary School (SLBN) is an extraordinary school located in the Regency of Karangasem, under the auspices of the Bali Provincial Government Education Office, providing proper education to students who have special needs. The responsibility for the success of the education of children with special needs in Karangasem SLBN lies in the hands of educators, namely Karangasem SLBN teachers. Special Education Teachers in Karangasem SLBN besides teaching, they also play a role in helping the development of their students. The education service model is an interesting study to study in an effort to meet the educational needs of Hinduism and Human Rights in children with special needs (ABK) in Karangasem SLBN amid the eruption of Mount Agung. Theories used to solve this research problem are behaviorism theory and humanistic learning theory.